Fulfill the Basic Rights of Indonesian Migrant Workers' Children in the Human Rights Perspective - Hijrah Lahaling (Faculty of Law, Musamus University, 2020)
The fulfillment of the basic rights of children of Indonesian Migrant Workers (PMI) left by their parents to grow and develop has not been optimally fulfilled either physically, mentally, psychologically, or socially. The right to fulfill the children of Indonesian migrant workers includes the right to survival, the right to education and the right to health. Neglect of the fulfillment of these rights is not yet fully in accordance with the 1945 Constitution of the Republic of Indonesia, Convention on the Rights of the Child, Law No. 6 of 2012, and Law No. 35 of 2014. This will certainly endanger the welfare and survival of PMI children in accordance with the principles of human rights. This research aims to formulate the fulfillment of the basic rights of children of Indonesian migrant workers in accordance with the principles of human rights.